Nitric Oxide as a Nephroprotective Agent in Cardiac Surgery - A. M. Boyko; N. O. Kamenshchikov; Yu. K. Podoksenov; M. L. Dyakova; Yu. S. Svirko; A. M. Gusakova; E. B. Kim; D. S. Panfilov; B. N. Kozlov (Общая реаниматология, 2025)
Aim. To evaluate the eﬃcacy of perioperative nitric oxide (NO) administration in reducing the incidence of acute kidney injury (AKI) during hemiarch surgery for nonsyndromic ascending aortic aneurysms under cardiopulmonary bypass and hypothermic circulatory arrest (HCA).Materials and Methods. A single-blind, prospective, randomized, controlled study included 80 patients older than 18 years who underwent hemiarch aortic surgery with HCA for nonsyndromic ascending aortic aneurysms between 2020 and 2023. Patients were randomized (1:1) into two groups: the NO group (who received perioperative NO at 80 ppm) and the control group (who received standard perioperative management without NO administration). The primary endpoint was the incidence of AKI according to KDIGO criteria. Secondary endpoints included biomarker levels of subclinical renal injury and clinical outcomes.Results. Postoperatively, the incidence of AKI was 25% in the NO group compared to 50% in the control group (OR=0.26; 95% CI: 0.10–0.69; P=0.036). Patients in the NO group had significantly lower levels of urinary neutrophil gelatinase-associated lipocalin (uNGAL, P=0.03) and cystatin C (P<0.001) 4 hours after surgery. In addition, the length of stay in the intensive care unit (ICU) was significantly shorter in the NO group (P=0.03) compared to the control group.Conclusion. Perioperative NO therapy at 80 ppm during hemiarch aortic surgery with HCA reduces the incidence of acute kidney injury, lowers the levels of kidney injury biomarkers (uNGAL and cystatin C), and shortens the ICU stay.